Rearing Ixodes scapularis, the Black-legged Tick: Feeding Immature Stages on Mice - Nuss, Andrew B. (J Vis Exp, 2017)
Ixodes scapularis, the vector of Lyme disease, is one of the most important disease vectors in the eastern and Midwestern United States. This species is a three host tick that requires a blood meal from a vertebrate host for each development stage, and the adult females require a blood meal for reproduction. Larval ticks attach to their host for 3 - 5 days for feeding and drop off the host when fully engorged. This dependency on several different hosts and the lengthy attachment time for engorgement complicates tick rearing in the laboratory setting. However, to understand tick biology and tick-pathogen interactions, the production of healthy, laboratory-reared ticks is essential. Here, we demonstrate a simple, cost-effective protocol for immature tick feeding on mice. We modified the existing protocols for decreased stress on mice and increased tick feeding success and survival by using disposable cages without mesh bottoms to avoid contact of ticks with water contaminated with mice urine and feces.